predictors need for complementary interventions using mobile application technology in women with breast cancer - Dewi, Inggriane; Tri Widianti, Anggriyana; Fatmawati, Ariani; Wulandari, Silfia; Indah Sarirudi, Tita (Jurnal Ners, 2023)
Background. Some women with breast cancer tend to have psycho-social stress, embarrassment from the disease's treatment, and difficulty asking for help. Furthermore, several studies indicate limited use of complementary online intervention in mental and spiritual health care, particularly when using mobile-based technologies. Purpose. This study identifies the key factors that affect the need for mobile-app complementary interventions and the variables affecting them among Indonesian breast cancer patients. Methods. A cross-sectional survey study with a simple random sampling technique included 112 patients between May and July 2022. The research instrument used is The Quality of Life-Breast Cancer questionnaire, Functional Assessment of Chronic Illness Therapy–Spiritual Well-Being (FACIT-Sp), Palliative Performa Scale Version 2, and The Need for Complementary Interventions using mobile-app technology (NCIM) to measure Predictors of The Need for Complementary Interventions. Meanwhile, multiple linear stepwise regression was used, and the potential multicollinearity effects among NCIM predictive variables were assessed through the collinearity analysis of variable inflation factors. Results. The mean score of NCIM was 25.17 and ranged from 10 to 40, and multiple regression analysis showed that the psychological and social dimensions of quality of life, as well as Facit-Sp, significantly affected the NCIM. This explains 8.5% of the total variance in the need for Mobile-app Complementary Intervention. Conclusion. Women with breast cancer have a high need for complementary interventions based on mobile technology. This study can provide the development of complementary intervention using mobile application technology.